2020
DOI: 10.3390/v12020175
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Interaction of Hepatitis B Virus with Mitochondria and Associated Proteins

Abstract: Around 350 million people are living with hepatitis B virus (HBV), which can lead to death due to liver cirrhosis and hepatocellular carcinoma (HCC). Various antiviral drugs/nucleot(s)ide analogues are currently used to reduce or arrest the replication of this virus. However, many studies have reported that nucleot(s)ide analogue-resistant HBV is circulating. Cellular signaling pathways could be one of the targets against the viral replication. Several studies reported that viral proteins interacted with mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 118 publications
(163 reference statements)
0
32
0
Order By: Relevance
“…A plausible metabolic link between mitochondria and influenza A, and with herpes viruses was shown in the 1950s by Ackerman and colleagues [ 13 , 14 ]. Recent studies showed how hepatitis B virus (HBV) [ 15 , 16 ] and hepatitis C virus (HCV) adopt the changes in mitochondrial dynamics for persistent infection [ 17 , 18 ]. Our laboratory has also shown that respiratory syncytial virus (RSV) infection affects mitochondrial function, leading to an altered immune response in lungs [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A plausible metabolic link between mitochondria and influenza A, and with herpes viruses was shown in the 1950s by Ackerman and colleagues [ 13 , 14 ]. Recent studies showed how hepatitis B virus (HBV) [ 15 , 16 ] and hepatitis C virus (HCV) adopt the changes in mitochondrial dynamics for persistent infection [ 17 , 18 ]. Our laboratory has also shown that respiratory syncytial virus (RSV) infection affects mitochondrial function, leading to an altered immune response in lungs [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the hepatitis B virus genome have been reported worldwide, and these mutations have been affecting the diagnosis of hepatitis B, the effectiveness of hepatitis B vaccination, and occasionally patient resistance to antiviral drugs for hepatitis B [27,30,[38][39][40]. Such mutations are known to influence the viral replication and pathophysiology, and thereby to be involved in occult HBV infection and persistence [9,12,[41][42][43]. On the other…”
Section: Discussionmentioning
confidence: 99%
“…Other reports identify alternative virus-host interactions that could be targeted. Hossain et al review the reported interactions between HBV proteins and mitochondrial signalling, with particular focus on innate immunity and viral replication [12]. They highlight several reported interactions between HBV and mitochondria that could be targeted to inhibit HBV replication, although exactly how this can be achieved remains unclear and is the subject of ongoing research.…”
mentioning
confidence: 99%